Impact of Digitalization on Firm Performance in the Manufacturing Sector: A Case Study of Nigeria - Chukwudi, Nkem (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the impact of digitalization on firm performance in the manufacturing sector: a case study of Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Digitalization has significantly impacted firm performance in Nigeria's manufacturing sector. It has enhanced operational efficiency, improved decision-making processes, and spurred innovation within firms. By embracing digital transformation, Nigerian manufacturing companies have bolstered their competitiveness and market positioning. Ongoing investment in digital capabilities is crucial for sustaining growth and success in the sector. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV) theory, technology acceptance model (TAM) & institutional theory may be used to anchor future studies on the impact of digitalization on firm performance in the manufacturing sector: a case study of Nigeria. Nigerian manufacturing firms should prioritize investment in digital infrastructure, talent development, and organizational culture conducive to digital innovation. Policymakers should enact supportive regulatory frameworks and incentives to encourage digitalization adoption among manufacturing firms in Nigeria.